Aerobic Fitness Is Associated With Cognitive Control Strategy in Preadolescent Children. Issue 2 (4th March 2017) - Kao, Shih-Chun; Drollette, Eric S.; Scudder, Mark R.; Raine, Lauren B.; Westfall, Daniel R.; Pontifex, Matthew B.; Hillman, Charles H.
ABSTRACT: The authors used a conditional accuracy function (CAF) method to compute the mean accuracy of multiple reaction time ranges, to investigate the association between aerobic fitness and the utilization of cognitive control strategy during preadolescence. Thirty-eight higher- and lower-fit children were grouped according to their cardiorespiratory capacity (VO2max ) and completed a modified flanker task. Seventeen young adults were recruited as a reference group of maturation. The results showed that higher-fit children exhibited an adult-like performance pattern, and demonstrated increased overall response accuracy compared to lower-fit children, with a disproportionally larger increase in individual responses when the time allowed for discriminative processing was constrained. These findings suggest that aerobic fitness is associated with enhanced cognitive control and development of a more proactive control strategy during flanker task in preadolescent children.